Consumer preferences for beef with improved nutrient profile() - Flowers, Sarah (J Anim Sci, 2019)
Although beef is a nutrient-rich foodstuff excelling in protein, vitamins, and minerals, there is controversy regarding the fat content of beef and its healthfulness in the diet. Although much of the fatty acid (FA) content in beef is considered “healthy fats,” many consumers are confused about the different classifications of FA. The objectives of this study were to determine consumers’ knowledge about the nutritional value of beef and its importance in purchasing decisions, and to gain a better understanding about preferences for changes in FA composition. Objectives of the study were completed through 2 consumer studies: 1) an online survey and 2) a taste-panel auction. In the online survey, respondents were asked to choose between 2 steaks that varied in polyunsaturated and saturated FA levels, iron content, and price. Respondents were also asked to categorize “Monounsaturated Fat,” “Polyunsaturated Fat,” “Saturated Fat,” and “Trans Fat,” as either “healthy” or “unhealthy” both before and after an educational excerpt was provided. The results from the online survey indicated many consumers are unclear about the differences in beef nutritional value, specifically FA content. Initially, only 66.4%, 69.1%, 79.1%, and 79.2% of respondents correctly categorized the monounsaturated, polyunsaturated, saturated, and trans fat, respectively. However, more than 90% of respondents correctly categorized the various FAs after an educational excerpt was provided. After survey respondents better understood the healthfulness of FA in beef, they were also willing to pay a premium for a steak with improved FA composition. However, these premiums diminished when participants had to actually put forth a monetary value for a steak in the taste-panel auction. Research shows that there is variation among cattle for FA composition. This provides opportunity to identify cattle with a favorable composition and market this product to the increasing population of health-conscious consumers. Our results provide insight for beef promotion and marketing opportunities and indicate that relaying information about FA content is extremely important to collect a premium for healthier beef.